Comparative Financial Performance of Companies in the Hotel, Restaurant, and Tourism Subsector Listed on the Indonesia Stock Exchange Before and During the COVID-19 Pandemic - Nurwiyanta Nurwiyanta; Andika Andika; Anisa Kusuma Hermatien; Kartinah Kartinah (Dinasti Publisher, 2023)
The objective of this study is to examine, quantify, and analyze the variations in the financial performance of companies operating in the hotel, restaurant, and tourism subsector that are listed on the Indonesia Stock Exchange (BEI). The analysis focuses on the years 2019 (pre-COVID-19) and 2020–2021 (during the COVID-19 pandemic). Key financial ratios, including the return on assets, the current ratio, the debt-to-equity ratio, and the total asset turnover, are employed to assess the companies' performance. The study's target population comprises hotel, restaurant, and tourism businesses operating between 2019 and 2021. Sample selection employs purposive sampling based on specific criteria. Data analysis encompasses descriptive statistical analysis and the Kolmogorov-Smirnov normality test, which reveals non-normal data distributions. Consequentially, a non-parametric hypothesis test, the Wilcoxon signed the rank test, is employed to determine differences. The findings indicate significant variations in return on assets, the current ratio, the debt-to-equity ratio, and the total asset turnover between the pre-pandemic year of 2019 and the pandemic years of 2020 and 2021.